Framework-building cold-water coral ecosystem characterisation: Key studies from macro- to micro-scale - Beuck, Lydia (2008)
Deep-water corals have been known for more than two centuries; however, broad scientific interest in these hardly accessible ecosystems is relatively new and strongly increasing in the last years owing to application of advanced technologies. Like their shallow-water counterparts, frame-building deep-water corals play a fundamental role in the ecology of the oceans. However, cold-water coral ecosystems have been already economically discovered and exploited by e.g., the fishing industry and jewellery industry and thus are regionally threatened. Therefore, primarily it is important to map and characterise their global distribution to deduce marine protected areas, which allow securing the oceans ecosystem balances, to establish ecologically sustainable fishing practises and to protect its potential as a rich pool for studies gaining human’s benefit. Additionally, it is essential to carry out base studies, which give insights into the biodiversity, biocoenotic interactions, the ecosystem functioning and history. The presented work attempts a cold-water coral ecosystem characterisation by different key studies on a macro and micro-scale with main focus on the North Atlantic and Mediterranean Sea. Within this context, this thesis presents a set of methodologies embedded into different key studies, some of them having been applied for the first time to this scientific field. The individual key studies are grouped thematically: (1) Cold-water corals as habitat-forming substrate (Chapter 2) and (2) interactions between substrate and its colonisers on a micro-scale (Chapter 3). Chapter 2 comprises four key studies with the main focus set on a general characterisation of cold-water coral ecosystems, in particular: (a) their abiotically triggered distribution to trace their individual environmental requirements; (b) the role of cold-water corals as habitat-forming substrate to investigate biodiversity, biocoenotic interactions and long-term influences of abiotic factors; (c) their bio-induced degradation mechanisms to ...